Six weeks of hip joint training using a novel multihip joint board improves sprint performance in competitive collegiate male sprinters - Nakata, H.; Nakanishi, Y.; Otsuki, S.; Mizuno, M.; Connor, J.; Doma, K. (The Journal of Strength and Conditioning Research, 2022)
In a previous study, we identified the possibility that hip joint training using a multihip joint board (MHJB) may increase the cross-sectional area (CSA) of the psoas major (PM) muscle and improve sprint performance. However, the preliminary study reported descriptive findings because of a limited sample size. Therefore, we aimed to investigate and statistically infer the effects of the MHJB training protocol with a larger sample of male collegiate sprinters. The sprinters were randomly assigned to either the MHJB group (n = 7) or the control group (n = 7). The MHJB protocol consisted of 7 separate exercises targeting the development of the hip musculature, all using the MHJB device. The MHJB group undertook the MHJB protocol 3 times per week for 6 weeks, after their normal daily workout, whereas the control group completed their normal daily workout without the MHJB protocol. Sprint performance was recorded from official 100-m competitions before, and after, the 6-week training period. At the end of the training period, significantly greater improvement in PM CSA and 100-m sprint was noted in the MHJB group compared with the control group. These findings confirm the efficacy of MHJB training for increasing PM CSA and improve sprint performance in competitive male sprinters.